Effectiveness of interventions for diagnosis and treatment of tuberculosis in hard-to-reach populations in countries of low and medium tuberculosis incidence: a systematic review. Issue 5 (May 2017) - Heuvelings, Charlotte C; de Vries, Sophia G; Greve, Patrick F; Visser, Benjamin J; Bélard, Sabine; Janssen, Saskia; Cremers, Anne L; Spijker, René; Shaw, Beth; Hill, Ruaraidh A; Zumla, Alimuddin; Sandgren, Andreas; et al.
Summary: Tuberculosis is over-represented in hard-to-reach (underserved) populations in high-income countries of low tuberculosis incidence. The mainstay of tuberculosis care is early detection of active tuberculosis (case finding), contact tracing, and treatment completion. We did a systematic review with a scoping component of relevant studies published between 1990 and 2015 to update and extend previous National Institute for Health and Care Excellence (NICE) reviews on the effectiveness of interventions for identifying and managing tuberculosis in hard-to-reach populations. The analyses showed that tuberculosis screening by (mobile) chest radiography improved screening coverage and tuberculosis identification, reduced diagnostic delay, and was cost-effective among several hard-to-reach populations. Sputum culture for pre-migration screening and active referral to a tuberculosis clinic improved identification. Furthermore, monetary incentives improved tuberculosis identification and management among drug users and homeless people. Enhanced case management, good cooperation between services, and directly observed therapy improved treatment outcome and compliance. Strong conclusions cannot be drawn because of the heterogeneity of evidence with regard to study population, methodology, and quality.